Near Eastern culture and society - Young, T. Cuyler (Theodore Cuyler), 1900-1976 (Princeton University Press, 2017)
Eleven scholars present a broad survey of Arabic-Islamic culture and society in the Near East. Art, literature, science, philosophy, religion, politics, international relations, and social problems are considered. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Islamic civilization.; SOCIAL SCIENCE -- Anthropology -- General.; Islamic civilization